Studies on Mechanical Properties of Schiffs Base Reinforced Epoxy Composites - Gunasekaran, Umamaheswari; Boopalan, M.; Umapathy, M.J.; V. Kanth, Swarna (Asian Journal of Chemistry, 2012)
Composites obtained from filler reinforcement of natural sources shows improved mechanical properties and impart biodegradation to the polymer. In the present work Schiffs base obtained from the oxidized dialdehyde product of guar gum and 3,5,-dimethyl aniline was used as reinforcing material for epoxy resin. The mechanical properties of virgin polymer were compared with composite with different filler concentration. It shows improvement in tensile, flexural, impact properties up to 3 % concentration of fillers, further increase in concentration shows decrease in the values could be due to the agglomeration of particles in the polymer matrix.